Water-moderated reactor fuel cladding reliability study - Бакутяк, Елена Викторовна; Пелых, Сергей Николаевич (Technology audit and production reserves, 2014)
Considering the fuel element, averaged by fuel assembly (FA) of water-moderated reactor with the power of 1000 MW (VVER-1000), the number of fuel elements with the greatest cladding failure probability after 4 operation years at Khmelnitsky NPP-2 (KNPP-2) is found. This will allow to calculate the fuel cladding failure probability and determine the most likely cladding damages, which will enable to improve the performance and economic indexes of VVER. The novelty of the paper lies in calculating the fuel cladding failure probability after 4 years of operation at KNPP-2 using a method, based on the energy version of the theory of creep (EVTP method). Up to date, this calculation for VVER of KNPP-2 was not performed. The reliability study of VVER-1000 fuel cladding failure was performed. As a result, the most probable number of failed fuel elements in the fuel assembly depressurize provided its location for 4 years in a fixed cell of the active core is found. Using these values it is possible to forecast fuel cladding failure probability. This will allow to get an idea about the reliability of nuclear reactor fuel elements under the given operating conditions.